We are not alone: the impact of externalities on public good provision - Christoph Engel; Bettina Rockenbach (Max Planck Institute for Research on Collective Goods, 2009)
Providing public goods is hard, because providers are best off free-riding. Is it even harder if one group's public good is a public bad for another group or, conversely, gives the latter a windfall profit? We experimentally study public goods provision embedded in a social context and find that in the absence of explicit norms externalities have almost no effect. With an endogenously formed provision norm positive as well as negative externalities dampen provision as compared to no externalities. We explain the surprisingly low provision under positive externalities by the providers' increased risk of inequity and stress the importance of institutions sustaining conditional cooperation.
Keywords: C91; D03; D43; D62; H23; H41; L13; 330; Public Good; Externality; Conditional Cooperation; Inequity Aversion; Norms